Semisolid liver infusion tryptose supplemented with human urine allows growth and isolation of Trypanosoma cruzi and Trypanosoma rangeli clonal lineages - Emanuella Francisco Fajardo; Marlene Cabrine-Santos; Keila Adriana Magalhães Ferreira; Eliane Lages-Silva; Luis Eduardo Ramírez; André Luiz Pedrosa (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
Abstract: INTRODUCTION This work shows that 3% (v/v) human urine (HU) in semisolid Liver Infusion Tryptose (SSL) medium favors the growth of Trypanosoma cruzi and T. rangeli. METHODS Parasites were plated as individual or mixed strains on SSL medium and on SSL medium with 3% human urine (SSL-HU). Isolate DNA was analyzed using polymerase chain reaction (PCR) and pulsed-field gel electrophoresis (PFGE). RESULTS SSL-HU medium improved clone isolation. PCR revealed that T. cruzi strains predominate on mixed-strain plates. PFGE confirmed that isolated parasites share the same molecular karyotype as parental cell lines. CONCLUSIONS SSL-HU medium constitutes a novel tool for obtaining T. cruzi and T. rangeli clonal lineages.